Prioritisation of surgery in the National Health Strategic Plans of Africa: a systematic review. (27th April 2015) - Citron, Isabelle; Chokotho, Linda; Lavy, Chris
Abstract: Background: Disease amenable to surgical intervention accounts for 11–15% of world disability and there is increasing interest in surgery as a global public health issue. National Health Strategic Plans (NHSPs) have been established in most countries and reflect their long-term health priorities, plans, and targets. To assess surgery's perceived importance in Africa, we reviewed its place in all such available plans. Methods: We analysed all 43 of the 55 independent countries in Africa that had NHSPs available in the public domain in March, 2014, in English or French. We searched for policies electronically with the search terms "surg*", "ortho*", "trauma", "cancer", "appendic*", "laparotomy", "HIV", "tuberculosis", and "malaria" and included those from 2002 to 2030. We then searched manually for disease prevalence, targets, and human resources. Findings: Eight (19%)of 43 NHSPs had no mention of surgery or surgical conditions. 28 (65%) of 43 had five or less mentions of surgery. HIV and malaria had 3801 mentions across all the policies compared with surgery with only 379 mentions. Trauma had 243 mentions, while the common surgical conditions of appendicitis, laparotomy, and hernia had no mentions at all. More than 95% (41 of 43) of NHSPs specifically mentioned the prevalences of HIV, tuberculosis, malaria, infant mortality, and maternal mortality. The most commonly mentioned surgical condition for which a prevalence was given was trauma, in only 47% (23 of 43) of policies. All NHSPs had plans and measurable targets for the reduction of HIV and tuberculosis and all but one had targets for malaria, maternal mortality, and child mortality. Of the 4232 health targets across 43 NHSPs, only 96 (2·3%) were related to surgical conditions or surgical care. 14 (33%) of 43 policies had no surgical targets. Interpretation: NHSPs are the best available measure of health service and planning priorities. It is clear from our findings that surgery is poorly represented and that surgical conditions and surgical treatment are not widely recognised as a public health priority. A paradigm shift is required if surgery is to be considered a public health concern, which should include greater prioritisation in national health strategic policies. Funding: None.